Pengaruh Leverage, Profitabilitas, dan Ukuran Perusahaan Terhadap Tax Avoidance - Owen Jonathan Pratama Sibarani; Emmiliana Hartanti (UNIVERSITAS KALBIS, 2022)
Tax avoidance is a process carried by companies to reducing tax burden so that profits can be obtained maximally without violating tax regulations. This research aims to analyze the influence leverage, profitability, and company size towards tax avoidance. The population in this research are all of the manufacturing companies basic industry & chemical sub – sector and consumer goods sub - sector listed on the Indonesia Stock Exchange (IDX) in the period 2016 - 2018. The sample selection by using purposive sampling and obtain a sample of 48 companies or 144 observation data. The data analysis method used in this research is multiple linear regression by using SPSS version 25. The simultaneously result showed that leverage, profitability, and company size do not affected towards tax avoidance. And the partially result showed that leverage do not affect toward tax avoidance, profitability affect toward tax avoidance, and company size responsibility affected toward tax avoidance.